Polycyclic aromatic hydrocarbons exposure and their joint effects with age, smoking, and TCL1A variants on mosaic loss of chromosome Y among coke-oven workers. (March 2020) - Liu, Yuhang; Bai, Yansen; Wu, Xiulong; Li, Guyanan; Wei, Wei; Fu, Wenshan; Wang, Gege; Feng, Yue; Meng, Hua; Li, Hang; Li, Mengying; Guan, Xin; et al.
Abstract: Mosaic loss of chromosome Y (mLOY) is the most common structure somatic event that related to increased risks of various diseases and mortality. Environmental pollution and genetic susceptibility were important contributors to mLOY. We aimed to explore the associations of polycyclic aromatic hydrocarbons (PAHs) exposure, as well as their joint effects with age, smoking, and genetic variants on peripheral blood mLOY. A total of 1005 male coke-oven workers were included in this study and their internal PAHs exposure levels of 10 urinary PAH metabolites and plasma benzo[a]pyrene-r-7, t-8, t-9, c-10-tetrahydotetrol-albumin (BPDE-Alb) adducts were measured. mLOY was defined by the median log R ratio(mLRR) of 1480 probes in male-specific region of chromosome-Y from genotyping array. We found that the PAHs exposure levels were linearly associated with mLOY. A 10-fold increase in urinary 1-hydroxynaphthalene (1-OHNa), 1-hydroxyphenanthrene (1-OHPh), 2-OHPh, 1-hydroxypyrene (1-OHP), ΣOH-PAHs, and plasma BPDE-Alb adducts could generate 0.0111, 0.0085, 0.0069, 0.0103, 0.0134, and 0.0152 decrease in mLRR-Y, respectively. Additionally, mLOY accelerated with age, smoking pack-years, and TCL1A rs1122138-C allele, and we observed the most severe mLOY among subjects carrying more than 3 of the above risk factors. Our results revealed the linear dose-effect associations between PAHs exposure and mLOY. Elder male smokers carrying rs1122138CC genotype were the most susceptible subpopulations to mLOY, who should be given protections for PAHs exposure induced chromosome-Y aberration. Graphical abstract: Image 1 Highlights: Increased levels of PAHs exposure were associated with more severe mLOY. PAHs, age, smoking pack-years, and TCL1A rs1122138CC had joint effects on mLOY. Take precautions against mLOY among elder smokers exposed to PAHs and rs1122138CC. Abstract : Increased levels of PAHs exposure were associated with more severe mLOY. There were interactive and joint effects of PAHs, age, smoking pack-years, and TCL1A rs1122138CC on mLOY.